2015
DOI: 10.1007/s00381-015-2614-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome after selective dorsal rhizotomy in children with spastic cerebral palsy

Abstract: SDR yields durable reduction in spasticity after 10 years. Early improvements in motor function are present, but at long-term follow-up, these improvements were attenuated in GMFCS II and III and were not sustained in GMFCS IV and V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 22 publications
6
48
0
4
Order By: Relevance
“…Seven out of the 16 studies evaluated the effect on spasticity specifically, and all reported sustained long‐term reduction or even normal muscle tone …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven out of the 16 studies evaluated the effect on spasticity specifically, and all reported sustained long‐term reduction or even normal muscle tone …”
Section: Resultsmentioning
confidence: 99%
“…With respect to the duration of the reduction in spasticity after SDR, only seven of the 16 studies analysed took a long‐term perspective . A sustained reduction of spasticity in most of the muscles evaluated was most often reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous prospective studies in a single, small sample of people who have undergone SDR have demonstrated reductions in spasticity, pain intensity, and pain interference that are maintained even years after SDR . Although previous studies have demonstrated short‐ and long‐term benefits of SDR in terms of reduced spasticity, prospective studies have differed over the benefit in functional outcomes . Furthermore, other than one study of 18 people that showed that SDR was related to relatively low pain and pain interference, we lack understanding of how SDR affects symptom experience as individuals age.…”
mentioning
confidence: 97%
“…4,5 Children with CP often have other associated impairments of sensation, perception, communication, cognition and behaviour. 4,5 Children with CP often have other associated impairments of sensation, perception, communication, cognition and behaviour.…”
Section: Spinal Dorsal Rhizotomy Plus Concurrent Left and Right Gastrmentioning
confidence: 99%